Design and application of chitosan-CuO nanocomposites synthesized via novel hybrid ionic gelation-ultrasonication methods for water disinfection. (April 2023) - Khoerunnisa, Fitri; Nurhayati, Mita; Herlini, Humaira; Adzkia, Qurratu Aini Alya; Dara, Fitri; Hendrawan, Hendrawan; Oh, Wen-Da; Lim, JitKang
Abstract: Chitosan‑copper oxide nanoparticles (NPCS-CuO) are widely used in various applications such as antimicrobial, catalysis, drug delivery, and nanotheranostics. In this study, the structures and antibacterial properties of chitosan-CuO nanocomposites is systematically investigated. NPCS-CuO was synthesized via hybrid ionic gelation-ultrasonication methods by means of solution mixing of copper oxide (NPCuO) and chitosan nanoparticles (NPCS) with citrate ion as a crosslinker. The synthesized NPCS-CuO were characterized by particle size analyzer (PSA), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and antibacterial activity tests. The synthesized NPCS-CuO has the smallest particle size of 195.3 nm with a polydispersity index (PDI) of 0.972 at the mass ratio of 30:0.005 correspond to NPCS and NPCuO, respectively. The interaction between CS and crosslinker predominantly occurred via hydrogen bonding of –NH and CO moieties, while interaction of NPCS and NPCuO took place via chelation between CO and CuO functional groups, as confirmed by FTIR spectra. The X-ray diffraction patterns revealed that the addition of NPCuO remarkably increased the crystallinity and in contrast reduced the crystallite size of NPCS. The NPCS-CuO exhibited superior antibacterial efficacy toward E. coli, S. aureus, and P. aeruginosa bacteria strains than that of NPCS where the maximum zone of inhibition and bacteria killing ratio reached up to 16 mm and 100 %, respectively. However, it showed the inferiority toward B. subtilis and S. typhi bacteria strains. These behaviors strongly controlled by the nature of each bacterial strain. Further studies in advanced characterizations and applications of NPCS-CuO as antibacterial agent is under investigation. Graphical abstract: Unlabelled Image Highlights: The hybrid method provides efficient way to prepare chitosan-CuO nanocomposites. NPCS and NPCuO interaction took place via chelation between CuO and citrate. NPCuO increased the crystallinity and reduced the crystallite size of NPCS. The NPCS-CuO exhibited superior antibacterial efficacy for water disinfection.